Teachers at the Forefront of SDGs: Awareness and Instructional Readiness of Secondary School Teachers in Ibadan Metropolis - S.O. Babalola; Adeniyi Michael Adeduyigbe (SEAQIS Journal of Science Education, 2026)
Sustainable development education has gained global prominence, yet there is limited empirical research on teachers’ awareness and readiness in the Nigerian secondary school context. Addressing this gap, the present study investigates the extent to which secondary school teachers in Ibadan Metropolis are aware of and prepared to teach sustainable development concepts. A descriptive survey design was employed using the Teachers’ Sustainable Development Awareness and Readiness Questionnaire (TSDARQ). Stratified and simple random sampling techniques were applied to select 300 practising teachers across public and private schools. Findings revealed high levels of awareness (M = 3.40, SD = 0.68) and readiness (M = 3.54, SD = 0.59), both exceeding the benchmark threshold of 2.50. However, systemic support and instructional resources remain insufficient to fully enable classroom integration. These findings provide initial empirical evidence from an under-researched Nigerian context and underscore the need for sustained professional development, provision of adequate instructional resources, and policy alignment. It is recommended that continuous training, curriculum integration, and adequate instructional resources be prioritised to empower teachers as effective drivers of sustainability education.